lndonesia-Europe Asymmetry Trade Agreement Post-Brexit UK - Catherine, Princes; Morgan, Anthony; Safira, Tania (PT. Riset Press International, 2023)
This study aims to estimate how the asymmetry of the agreement between the UK and Indonesia post-Brexit. A literature review on international trade agreements was carried out by tracing agreement data stored in the database of the Indonesian Ministry of Foreign Affairs in the 2010-2019 period. The result is that there is only one trade agreement between Indonesia and the UK, which is related to the Fourth Stage Multi-stakeholder Forestry Program (4th-MFP) project. In the same period, Indonesia also participated in a trade agreement with the European Union called the Voluntary Partnership Agreement - Forest Law Enforcement Governance and Trade (VPA-FLEGT). The VPA-FLEGT is asymmetric in favor of the European Union while the MFP is asymmetric in favor of Indonesia. After analyzing the two agreements, it was found that the tendency is that the UK will continue to encourage asymmetry due to its strict environmental laws and large demand for timber. The asymmetry will encourage Indonesia to continue supplying Britain with timber from legal sources post-Brexit.